HUBUNGAN ANTARA KEMAMPUAN MENYUSUN PARAGRAF DAN MOTIVASI BERPRESTASI DENGAN KETERAMPILAN MENULIS LAPORAN - Haryanto Haryanto (Jurusan Tadris Bahasa Indonesia, 2016)
This study aimed to determine whether there is (a) the relationship between the ability to develop paragraphs and report writing skills, (2) the relationship between achievement motivation and skills to write reports, and (3) the relationship between ability and achievement motivation arrange paragraphs together with the skills write reports. This research was conducted at SMK Negeri 1 Sukoharjo, January to June 2010. The research method used is survey method with correlation techniques. The population was eleventh grade students of SMK Negeri 1 Sukoharjo. The sample of 60 people taken by simple random sampling. Instruments to collect data is a test of skills to write reports, prepare ability test paragraph, and achievement motivation questionnaire. Data analysis techniques used are statistical techniques of regression and correlation (simple and double). The results showed that: (1) there is a positive correlation between the ability to develop paragraphs and report writing skills (r = 0.79 Y.1 the real level Î± = 0.05 with N = 60 where rt = 0.254), (2) there was a positive relationship between achievement motivation and report writing skills (r = 0.68 at Y.2 real level Î± = 0.05 with N = 60 where Avg. = 0.254), and (3) there was a positive correlation between the ability to develop paragraphs and achievement motivation, together with the skills to write reports (R y.12 = 0.87 at Î± = 0.05 significant level with N = 60 where rt = 0.254). From the above results can be stated that individually or jointly develop the ability and achievement motivation paragraphs made a significant contribution to the skills to write reports. This indicates that these two variables can be a good predictor for the skills to write reports.